Enhancing soil organic carbon, particulate organic carbon and microbial biomass in semi-arid rangeland using pasture enclosures - Oduor, C.O.; Karanja, N.K.; Onwonga, R.N.; Mureithi, Stephen M.; Pelster, David E.; Nyberg, G. (Springer, 2018)
Rehabilitation of degraded rangelands through the establishment of enclosures (fencing grazing lands) is believed to improve soil quality and livelihoods, and enhance the sustainability of rangelands. Grazing dominated enclosure (GDE) and contractual grazing enclosure (CGE) are the common enclosure management systems in West Pokot County, Kenya. Under CGE, a farmer owning few animals leases the enclosure to households with relatively more livestock, while GDE is where the livestock utilizing the enclosure are purely owned by the farmer. Livestock management in both systems is via the free-range system. This study evaluated the effect of enclosure management on total soil organic carbon (SOC), particulate organic carbon (POC) and microbial biomass carbon (MBC) and nitrogen (MBN) as key indicators of soil degradation at 0-40 cm depth. The two enclosure systems were selected based on three age classes (3-10, 11-20 and > 20 years since establishment) (n = 3). The adjacent open grazing area (OGR) was used as a reference (n = 9).Relative to OGR, the pasture enclosures significantly decreased soil bulk density and increased the concentrations of total organic C, POC, MBC and MBN compared to the degraded OGR (P < 0.001). Significantly higher concentrations of POC and MBC was recorded in GDE than CGE (P = 0.01). The POC accounted for 24.5-29.5% of the total SOC. MBC concentrations ranged from 32.05 ± 7.25 to 96.63 ± 5.31 µg C g-1 of soil in all grazing systems, and was positively correlated with total SOC and POC (P < 0.001). The proportional increase in POC and MBC was higher in GDE (56.6 and 30.5% respectively) compared to CGE (39.2 and 13.9% for POC and MBC respectively).This study demonstrated that controlling livestock grazing through the establishment of pasture enclosures is the key strategy to enhance total SOC, POC, MBC, and MBN in degraded rangelands; a precondition for improving soil quality. Therefore, the establishment of enclosures is an effective restoration approach to restore degraded soils in semi-arid rangelands.